The Effects of Catholic Secondary Schooling on Educational Achievement - Neal, Derek (Journal of Labor Economics, 1997)
This article examines the effect of Catholic secondary schooling on high school graduation rates, college graduation rates, and future wages. The article introduces new measures of access to Catholic schools that serve as potential instruments for Catholic school attendance. Catholic secondary schools are geographically concentrated in urban areas and Catholic schooling does increase educational attainment significantly among urban minorities. The gains from Catholic schooling are modest for urban whites and negligible for suburban students. Related analyses suggest that urban minorities benefit greatly from access to Catholic schooling primarily because the public schools available to them are quite poor. Copyright 1997 by University of Chicago Press.